Retratos da docência em textos de revista: expectativas, papel social e emancipação, um estudo comparativo entre letras e educação física - Amaral, Joseane (2012)
The study of social role involves the analysis the structures of expectations that surrounds it. Considering that social roles are clusters of expectations connected to the behavior of people in a certain society (Dahrendorf, 1969), it is important to know the level of the expectations - cognitive or normative (Luhmann, 1983). And how it is reflected in the society mentioned. This study aims to discover discursive evidences on the constitution's expectations that demarcate the social role of Languages professional, as opposed to Physical Education professional. Through corpora collected from magazines, we have started the analysis using Corpus Linguistics approach. The Corpus Linguistics works with computerized corpora, exposing linguistic evidence, questioning paradigms and showing new ways to the researcher (Berber Sardinha, 2004). For this purpose, we used two tools - the WordSmith Tools by Mike Scott, and the Semantic Mapper, by Richter and Berber-Sardinha. Our motivation for this study came from the knowledge that there is no specific legislation for accurate defining and delimitating the guidelines of Languages profession; the situation is reversed in the Physical Education profession, which is emancipated according to Brazilian Law nº 9696/98. Thus, we aim to discover how the social role can be "read" by analyzing texts from magazines, and how this discourse migrates and constitutes the respective social role. We study how the mass media exposes, and somehow imposes conduct and behavior patterns, as the "ready-made formulas" that teachers must follow as a basis. We adopt as the research parameters the Holistic Theory of Activity Extended, version 3.0, by Richter (2008, 2010b). This study is a pilot for the extended version of THA. We initiated the study of the Attribution Factors, a set of variables related to the notion of social roles, institutional spaces, functions, competencies, role models and group belonging. The results suggest the presence, in the analyzed corpora, of differentiation trades between; on the one hand the visibility of the emancipated professions, through the demonstration of recognition and the endogenous discourses; and on the other hand, the analysis shows the exogenous discourse, characteristic of the professions without a self institutional place.